N. Streletskyi (1885-1967) – a specialist in the field of building structures and bridge construction - Podkoshanaia, O. N. (History of science and technology, 2017)
The article highlights the life and work of a talented Soviet scientist – N. Streletskyi. Through his works he wrote brilliant pages in the history of building art, in the development of communication, bridge construction and native science and technology in general. The main directions of his scientific researches are outlined, the practical, public and pedagogical activity of the scientist is analyzed.